Prevalence and Factors associated with Caesarean Section in Gynecology Unit of Ayub Teaching Hospital, Abbottabad - Shaheen, Ambrina; Rasheed, Sana; Sayyad, Hajra; Bibi, Saima; Batool, Fatima; Khan Wazir, Salma; Zarqaish (Indus Journal of Bioscience Research, 2024)
Background: Cesarean section (CS) is a crucial surgical procedure in modern obstetrics, typically performed due to factors like dystocia, prior CS, fetal distress, and multiple gestations. While CS can be life-saving, it carries risks such as post-delivery complications, financial burdens, and potential psychological impacts on mothers. Objective: This study investigates the prevalence and factors influencing CS among women at Ayub Teaching Hospital, Abbottabad. Materials and Methods: This is a descriptive cross-sectional study done in Gynecology C unit of Ayub Teaching Hospital, Abbottabad from 21st July, 2024 to 08th Sept, 2024 after taking approval from ethical committee. 316 patients who underwent delivery by various methods were included in this study. Basic demographics and type of procedure were noted after taking consent from the patient. SPSS version 23.0 was used Results: The overall prevalence of caesarean section was around 51.58% in our study. Age of mother more than 35 years (OR: 1.33, 95% CI: 0.605-2.966), post term (OR: 1.99, 95% CI: 0.596.726), high parity (OR: 2.1, 95% CI: 1.116-3.962), large baby size (OR: 3.45, 95% CI: 0.38-31.48) and secondary education (OR: 1.25, 95% CI: 0.567-2.785) were found to increase odds of caesarean section, whereas female sex (OR: 0.91, 95% CI: 0.587-1.429) , small baby size (OR: 0.75, 95% CI: 0.473-1.282), preterm labor (OR: 0.82, 95% CI: 0.524-1.295) and age group 25-34 (OR: 0.91, 95% CI: 0.554-1.455) were found to decrease the risk of caesarean section. Conclusion: Prevalence of caesarean section was found to be increasing in local population. The results highlight the impact of clinical and cultural factors on delivery choices, stressing the need for tailored maternal healthcare planning.